The Impact of the Pertamina Patra Niaga Aviation Fuel Terminal (AFT) Ahmad Yani's Social & Environmental Responsibility Program on the Satisfaction Level of Cooperative Members: Financial, Marketing, and Human Resources Perspectives - Afifa Azka Putri; Evelin Bertua Nababan; Fadyana Aida Hamansyur; Moh Khoiruddin; M Rinaldy Putra (Global Writing Academica Researching and Publishing, 2025)
The Mangunharjo sub-district is facing serious challenges due to tidal flooding that has transformed the livelihoods of its residents from rice farmers to shrimp farmers. In response to this situation, PT Pertamina Patra Niaga Aviation Fuel Terminal Ahmad Yani launched a Social and Environmental Responsibility CSR) program titled Mami Sera (Mangunharjo Mandiri Sejahtera) through the Koperasi Trengginas Jaya Abadi. This program is aimed at empowering the local community, especially MSME actors and farmers. This research aims to analyze the impact of the Corporate Social Responsibility program on the level of satisfaction of members of the Trengginas Jaya Abadi coorperative group from the perspectives of finance, marketing, and human resources (HR). The method used is a descriptive quantitative approach with a Likert scale questionnaire instrument administered to 40 cooperative members. The t-test results show that only the HR aspect has a significant impact on member satisfaction (t-count 4.322 > t-table), while the financial and marketing aspects do not have an individual impact. However, through the simultaneous F-test, all three aspects together have a significant impact on member satisfaction (sig. 0.000). These results emphasize the importance of strengthening the HR aspect in the Corporate Social Responsibility program and the need for a comprehensive evaluation to ensure the program's impact is more equitable and effective.